Conversations about the Environment - Burton, Howard (Ideas Roadshow Collections., 2021)
Conversations About The Environment is a five-part Ideas Roadshow Collection of carefully-edited Ideas Roadshow Conversations featuring leading experts with a detailed preface highlighting the connections between the different books. All five books include a detailed essay setting up the different ideas and questions for discussion at the end of each chapter. The following experts have participated in this Collection: 1. Joanna Haigh, Professor Emerita of Atmospheric Physics at Imperial College London and Co-Director of the Grantham Institute;2. Andy Hoffman, Holcim Professor of Sustainable En.